2018
DOI: 10.1007/s10157-018-1591-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of essential amino acid кetoanalogues and protein restriction diet on morphogenetic proteins (FGF-23 and Кlotho) in 3b–4 stages chronic кidney disease patients: a randomized pilot study

Abstract: LPD + KA provides support for nutrition status and contributes to more efficient correction of FGF-23 and Klotho abnormalities that may result in cardiovascular calcification and cardiac remodeling decreasing in CKD. At the same time, a prolonged LPD alone may lead to malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
0
24
2
1
Order By: Relevance
“…The nephroprotective effect in acute damage observed in our study has not been previously reported. This study opens up the possibility of essential amino acid α-keto acid analogs efficacy in both acute and chronic kidney disease damage 24 .…”
Section: Resultsmentioning
confidence: 87%
“…The nephroprotective effect in acute damage observed in our study has not been previously reported. This study opens up the possibility of essential amino acid α-keto acid analogs efficacy in both acute and chronic kidney disease damage 24 .…”
Section: Resultsmentioning
confidence: 87%
“…Among these, 115 studies were eliminated with reasons. The remaining 12 studies, published between 1994 and 2018, were included in this meta-analysis [7,14,15,16,17,18,19,20,21,22,23,24]. Characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we do not know if a supplementation of KA alone without low protein diets has any benefit on metabolic disturbances related to CKD. Few studies [3,4,5,6,7] compared KAs supplementation with the same protein restriction and it is difficult to decipher if “KAs effects” are solely the consequence of a decrease of protein intake or if they act specifically. Another interrogation is the reproducibility of the diet composition in different groups.…”
Section: Potential Benefit Of Ketoacid Analoguesmentioning
confidence: 99%